An indicator framework for assessing the readiness of hospital in the smart healthcare transformation. Issue 7 (1st November 2022) - Zhao, X; Ge, B
Abstract: The technical and management issues that existed in traditional healthcare institutions, such as relatively lagging technologies, untimely information, have received increasing attention. In recent decades, the reconstruction or transformation of smart healthcare system has emerged as a new research trend. Especially with the outbreak of the COVID-19 epidemic, the smart healthcare system realizes the timely allocation of medical resources and sharing of information. Therefore, this paper aims to develop an indicator framework for assessing the hospital's readiness in transforming towards smart healthcare. First, based on the literature review, an indicator framework of readiness of smart healthcare transformation is developed for smart healthcare transformation, which includes three hierarchies of " smart facility management (smart FM)", "medical system (MS)" and "organizational management (OM)". Secondly, an online questionnaire survey is conducted to test the validity of the indicator framework. Based on factor analysis, the indicator framework is proved to be effective as a whole, and all the 26 indicators are significant. Finally, the readiness of case hospital "A" in the smart healthcare transformation is examined by fuzzy synthetic evaluation method. The findings of this paper provide an assessment tool for medical institutions to self-evaluate their status in the information construction process.